2020
DOI: 10.1111/all.14149
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for c‐Myc in group 2 innate lymphoid cell activation

Abstract: Background: Asthma is a complicated chronic inflammatory disorder characterized by airway inflammation and bronchial hyperresponsiveness. Group 2 innate lymphoid cells (ILC2) are tissue-resident innate effector cells that can mediate airway inflammation and hyperresponsiveness through production of IL-5, IL-13 and VEGFA. ILC2 in asthma patients exhibit an activated phenotype. However, molecular pathways that control ILC2 activation are not well understood.Methods: MYC expression was examined in ILC2 sorted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
(108 reference statements)
0
28
0
Order By: Relevance
“…It was recently verified that c-Myc expression is upregulated in group 2 innate lymphoid cells (ILC2s) in the blood of asthma patients. Using a mouse model of allergic inflammation, it was found that inhibition of c-Myc repressed ILC2 activity, causing reduction in airways inflammation and other pathogenic responses [ 54 ]. These findings suggest that targeting c-Myc may unlock novel strategies to combat asthma.…”
Section: C-myc As a Therapeutic Target In Other Diseasesmentioning
confidence: 99%
“…It was recently verified that c-Myc expression is upregulated in group 2 innate lymphoid cells (ILC2s) in the blood of asthma patients. Using a mouse model of allergic inflammation, it was found that inhibition of c-Myc repressed ILC2 activity, causing reduction in airways inflammation and other pathogenic responses [ 54 ]. These findings suggest that targeting c-Myc may unlock novel strategies to combat asthma.…”
Section: C-myc As a Therapeutic Target In Other Diseasesmentioning
confidence: 99%
“…In addition, c-Myc is a basic helix-loop-helix transcription factor mainly responded to IL-33, IL-25 and TSLP, which is closely related to the activation and pathogenicity of ILC2s in vivo . The activation of ILC2s results in the upregulation of c-Myc expression, which leads to proliferation and cytokine production of ILC2 ( 38 ). The AP-1 superfamily basic leucine zipper transcription factor, activating transcription factor-like (BATF) potentially regulates ILC2s.…”
Section: Initiation Of the Ilc2 Response During Allergic Reactionsmentioning
confidence: 99%
“…Microarray and pathway enrichment analyses revealed that MYC expression could be downregulated by 1,2,3,4,6-penta-O-galloyl-beta-D-glucopyranoside (PGG) in hepatocellular carcinoma [78]. Using a genome-wide microarray analysis, it was reported that targeting c-Myc would unlock novel strategies to combat asthma [79]. β-catenin could be deemed as an anticancer therapeutic target by regulating c-Myc and CDKN1A expression in breast cancer cells [80].…”
Section: Undruggable To Druggable Proteins Using Microarraysmentioning
confidence: 99%